Consejo universitario. - Universidad Estatal a Distancia (San José, Costa Rica : UNED, 2024)
De izquierda a derecha José Antonio Blanco, Ramiro Porras, Fernándo Brenes Espinoza, María Eugenia Bozzoli Vargas, Don Rodrigo Arias Camacho, Marlen Víquez Salazar, Juan Carlos Parreaguirre Camacho y Carlos Morgán Marín
Colección Fototeca UNED
Keywords: Blanco, José Antonio; Porras, Ramiro; Brenes Espinoza, Fernándo; Bozzoli Vargas, María Eugenia; Arias Camacho, Rodrigo -- Rector -- 1999-2009; 2019-2024; 2024-; Víquez Salazar, Marlen; Parreaguirre Camacho, Juan Carlos; Morgán Marín, Carlos; FOTOGRAFÍAS; UNIVERSIDAD ESTATAL A DISTANCIA -- COSTA RICA; FOTOTECA; ACTIVIDAD